Effects of within‐ and between‐person assessments of alcohol expectancies and valuations on use and consequences moderated by sex. (17th September 2021) - Schultz, Nicole R.; Graupensperger, Scott; Lostutter, Ty W.
Abstract: Background: Alcohol expectancies (AE; beliefs about the likelihood of outcomes) and valuations (beliefs about the desirability of outcomes) may help explain alcohol use by young adults. However, it remains unclear how variability in AE and valuations over time are related to alcohol‐related outcomes, and whether these associations are moderated by sex. The current study addressed these gaps in knowledge by examining within‐person variability among positive and negative AEs, valuations, and alcohol‐related outcomes over a 12‐month period. Methods: Data were collected from 433 college students ( M age  = 20.06; 59.81% women) who completed surveys at 4 timepoints: at baseline and 3‐month, 6‐month, and 12‐month follow‐up. Results: We found substantial within‐person variability in both AE and valuations (intraclass correlation coefficients ranged from 50% to 66%), and differences in variability by sex, with women showing more variability than men. Multilevel models revealed that weekly drinking was significantly higher at timepoints in which participants held relatively greater AE for sociability, sexuality, and risk/aggression, but lower when participants expected greater effects on self‐perception. Weekly drinking was also higher when participants reported more favorable valuation of risk/aggression. Participants experienced significantly more negative consequences at timepoints in which they held relatively greater AE for sexuality and self‐perception. No AEs were associated with a reduced likelihood of negative consequences. Participants experienced more negative consequences at timepoints in which they reported more favorable valuation of self‐perception No valuations were associated with fewer consequences. Several between‐ and within‐person associations were moderated by sex. Conclusions: These findings suggest that AE and valuations are dynamic, that young adults' beliefs about the effects of alcohol varied over time, and that both negative and positive AE and valuations may be important correlates of alcohol use and consequences. These findings have implications for interventions designed to challenge expectancies and valuations with the goal of reducing alcohol use and associated consequences. Abstract : The current study assessed between‐ and within‐person variability in alcohol expectancies and valuations in relation to alcohol‐related outcomes, and whether these associations were moderated by sex using longitudinal data. Multilevel models showed that fluctuations in positive and negative expectancies and valuations were associated with weekly drinking and negative consequences, with several associations moderated by sex. Expectancies and valuations are dynamic beliefs that are important antecedents to alcohol‐related outcomes, which has important implications for clinical interventions aimed at challenging these beliefs.